Nota de los coordinadores de este monográfico - Jorge Costa Delgado; Liliane López-Rabatel; José Luis Moreno Pestaña; Yves Sintomer (Daimon)
Nota de los coordinadores Jorge Costa Delgado, Universidad de Cádiz Liliane López-Rabatel, Institut de Recherche sur l’Architecture Antique José Luis Moreno Pestaña, Universidad de Cádiz Yves Sintomer, Université de Paris 8, Institut Universitaire de France